Current State-of-the-Art 3D MRI Sequences for Assessing Bone Morphology with Emphasis on Cranial and Spinal Imaging: A Narrative Review - Kavrakova, Irena Georgieva; Haage, Patrick; Stueckle, Christoph Alexander (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2025)
Traditionally, CT has been the go-to method for visualizing bone structures, while MRI has been preferred for assessing soft tissues, because structures containing tightly bound water molecules – such as bones, tendons, cartilage, and ligaments – produce a rapidly decaying T2* signal, which conventional MRI sequences fail to capture. To address this limitation, spoiled gradient echo sequences were refined, and short-TE sequences were introduced, enabling radiation-free bone imaging. This advance is particularly crucial for pediatric patients and in scenarios where an MRI-only approach is preferred, such as in radiation-sensitive cases and surgical planning.A comprehensive literature review was conducted by searching the PubMed and Google Scholar databases, using specific keywords: “black bone MRI” or “sCT bone” (Synthetic CT), “ZTE” (zero echo time), “UTE” (ultrashort echo time), “VIBE” (Volumetric Interpolated Breath-hold Examination), “FRACTURE” (FFE resembling a CT using restricted echo-spacing) and for title and abstract queries. The selection criteria included scientific articles published in English and German. The research was focused on the advances of the past five years in the application of the sequences in the area of the skull and spine. To support the technical understanding, earlier publications were also examined to offer readers essential background on the fundamental principles of the sequences, helping them better comprehend recent advances. For the investigation of the recent applications of the sequences, a narrow five-year time frame was applied, resulting in approximately 250 findings. From these, publications focused on the skull and spine regions were selected, with an emphasis on covering various pathologies and a preference for studies that compare different gradient echo sequences. To explore the technical aspects of the sequences, a broader time frame of ten years was selected, yielding approximately 868 results. From these, studies with more general explanations – avoiding in-depth physical and computer science details – were chosen. Using these selection parameters, 69 studies were highlighted.The gradient echo technique enables rapid and adaptable imaging, which can be customized to highlight specific tissue types. Spoiled GRE sequences such as VIBE, STAR/VIBE, and FRACTURE provide enhanced bone-to-soft tissue contrast, particularly when used with Dixon reconstruction. Short-TE sequences like UTE and ZTE utilize fast gradient switching, low flip angles, and non-Cartesian acquisition to improve bone visualization while suppressing soft tissue signals. These methods can effectively detect traumatic, neoplastic, and degenerative changes, offering CT-like imaging capabilities when patient-specific factors and the region or pathology of interest are properly considered. Additionally, integrating bone-selective sequences with deep learning could further enhance diagnostic accuracy and potentially replace CT.
Keywords: BlackBone MRI; ZTE; UTE; VIBE; FRACTURE; sCT